Corrupt Practices of Prisoners (Initial Research Results) (Archives of Criminology, 2006)
An analysis of the research questionnaires shows that most respondents (64%) think corruption is a significant problem of the Prison Service. Twenty-eight respondents (14%) quoted having received a corruption offer from a convict. If we consider the fact that one out of 7 respondents received a corruption offer and every second respondent thinks corruption is a significant issue, such an assessment does not reflect the experience of most people who deemed corruption a significant issue, but rather their feelings of threat or concern. Certainly, such feelings might be influenced by the multitude of such information in the media. In the newspapers, and inthe Penitentiary Forum which reaches every Prison Service member in particular, there are detailed accounts of specific cases of corrupt practices that were uncovered. As concerns corruption offers, we have to underline that they were twice more frequently addressed to warders than to counsellors. As stated in the survey, 19 warders and 9 counsellors admitted having received such offers. The fact that corruption offers were more often addressed at warders than counsellors might be explained to some extent by the fact that prisoners have more contact with the warders than the counsellors (prison yard, baths).